2022
DOI: 10.3389/fsurg.2022.948026
|View full text |Cite
|
Sign up to set email alerts
|

Clinical characteristics and survival outcomes of patients with pneumonectomies: A population-based study

Abstract: BackgroundPrognostic factors in a pneumonectomy (PN) are not yet fully defined. This study sought to analyze and evaluate long-term survival after pneumonectomies (PNs) for patients with non-small cell lung cancer (NSCLC).MethodsWe obtained data from the Surveillance, Epidemiology, and End Results (SEER) database for patients who underwent PNs between 2004 and 2015. Propensity score matching (PSM) analysis and Kaplan–Meier curves were used to estimate overall survival (OS), while univariate and multivariable C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 41 publications
0
1
0
Order By: Relevance
“…The diagnosis of LCLC is more difficult due to the small sample size obtained by transbronchial lung biopsy and the fact that LCLC can only be diagnosed in surgically resected tumors [2,6]. Some previous studies have shown that the prognostic factors affecting lung cancer are mainly the American Joint Committee on Cancer (AJCC) stage, surgery, tumor size, chemotherapy, and level of differentiation [7,8]. Generally, surgery remains the standard of care for stage I lung cancer patients, and stereotactic radiotherapy is the standard for those who cannot undergo surgical resection [9].…”
Section: Introductionmentioning
confidence: 99%
“…The diagnosis of LCLC is more difficult due to the small sample size obtained by transbronchial lung biopsy and the fact that LCLC can only be diagnosed in surgically resected tumors [2,6]. Some previous studies have shown that the prognostic factors affecting lung cancer are mainly the American Joint Committee on Cancer (AJCC) stage, surgery, tumor size, chemotherapy, and level of differentiation [7,8]. Generally, surgery remains the standard of care for stage I lung cancer patients, and stereotactic radiotherapy is the standard for those who cannot undergo surgical resection [9].…”
Section: Introductionmentioning
confidence: 99%